A Review on the Importance of Microbial Biopolymers Such as Xanthan Gum to Improve Soil Properties - Mendonça, Amanda (2020)
Chemical stabilization of soils is one of the most used techniques to improve the properties of weak soils in order to allow their use in geotechnical works. Although several binders can be used for this purpose, Portland cement is still the most used binder (alone or combined with others) to stabilize soils. However, the use of Portland cement is associated with many environmental problems, so microbiological-based approaches have been explored to replace conventional methods of soil stabilization as sustainable alternatives. Thus, the use of biopolymers, produced by microorganisms, has emerged as a technical alternative for soil improvement, mainly due to soil pore-filling, which is called the bioclogging method. Many studies have been carried out in the last few years to investigate the suitability and efficiency of the soil–biopolymer interaction and consequent properties relevant to geotechnical engineering. This paper reviews some of the recent applications of the xanthan gum biopolymer to evaluate its viability and potential to improve soil properties. In fact, recent results have shown that the use of xanthan gum in soil treatment induces the partial filling of the soil voids and the generation of additional links between the soil particles, which decreases the permeability coefficient and increases the mechanical properties of the soil. Moreover, the biopolymer’s economic viability was also analyzed in comparison to cement, and studies have demonstrated that xanthan gum has a strong potential, both from a technical and economical point of view, to be applied as a soil treatment.